DAYA TARIK LAGU BAGI ANAK USIA DINI: STUDI KASUS DI TK PERTIWI I SINGODUTAN, WONOGIRI - wicaksono, refi yunanda; Utomo, Udi (Universitas Negeri Semarang, 2017)
Music can be defined as voices or sounds that rhythmic rapidly in the form of song by the attractive and fun tones, rhythm, melody and harmony for the listener. Music is able to influent the listeners’ emotion, including the children. This research is aimed to know, to describe and to conclude the attractive things of a song to the students of TK Pertiwi 1 Singodutan. This research is a qualitative research. The techniques used for collecting the data are observation, interview, and documentation. The result of this research are: (1) the characteristic of the song’s melody that is interesting for the children (2) the song’s lyrics that is suitable with the children’s knowledge, (3) the content of the song’s lyrics that is suitable with the children’s experience, (4) the existence of the stimulant along with the song.